Pancreatic organogenesis mapped through space and time - Marissa A. Scavuzzo; Wojciech J. Szlachcic; Matthew C. Hill; Natalia M. Ziojla; Jessica Teaw; Jeffrey C. Carlson; Jonathan Tiessen; Jolanta Chmielowiec; James F. Martin; Malgorzata Borowiak (Experimental and Molecular Medicine)
Abstract The spatial organization of cells within a tissue is dictated throughout dynamic developmental processes. We sought to understand whether cells geometrically coordinate with one another throughout development to achieve their organization. The pancreas is a complex cellular organ with a particular spatial organization. Signals from the mesenchyme, neurons, and endothelial cells instruct epithelial cell differentiation during pancreatic development. To understand the cellular diversity and spatial organization of the developing pancreatic niche, we mapped the spatial relationships between single cells over time. We found that four transcriptionally unique subtypes of mesenchyme in the developing pancreas spatially coordinate throughout development, with each subtype at fixed locations in space and time in relation to other cells, including beta cells, vasculature, and epithelial cells. Our work provides insight into the mechanisms of pancreatic development by showing that cells are organized in a space and time manner.